Zum Theater als kultureller Lernort. Mit einigen Überlegungen über Augusto Boals Teatro do oprimido - Fiorentino, Francesco (Kritik. Rivista di letteratura e critica culturale, 2023)
This article presents, in a slightly revised version, materials used for my seminar Theater als Ort der Fremd-Erfahrung. Transkultureller Ansatz und Dramapädagogik, which took place in July 2021 as part of the online-master DaF-DaZ-Didaktik at Suor Orsola Benincasa University of Naples. The article offers introductory reflections on the subject of theatre as a transcultural place of learning, which can be adopted in secondary school. First of all, I tried to define the concept of transculturality more closely and to distinguish it from the concepts of multiculturalism and interculturality. Secondly, I make some comments relating the practice of blackfacing as an example of unconscious or – as one could also say – structural racism. Finally, I explain Augusto Boal’s theatre concept through his Theatre of the Oppressed.